(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rationale, Language, and Meaning comprises of two volumes which might be perused freely of one another volume I, An Introduction to Logic, and volume 2, Intentional Logic and Logical Grammar. Together they involve a study of present day rationale from the point of view of the examination of characteristic language. They speak to the consolidated endeavors of two scholars, two rationalists, and one etymologist. An endeavor has been made to coordinate the commitments of these distinctive controls into a solitary steady entirety. This venture was roused by a conviction shared by the majority of the creators, to be specific that rationale and language curve indivisible, especially with regards to the investigation of importance. Logic is introduced from a linguistic perspective in volume 1, although an attempt has been made to keep things interesting for readers who just want to learn logic (perhaps with the exception of those with a purely mathematical interest in the subject). Thus some subjects have been included which are not to be found in other introductory texts, such as many-valued logic, second order logic, and the relation between logic and mathematical linguistics. Also, a first attempt is made at a logical pragmatics. Other and more traditional subjects, like the theory of definite descriptions and the role of research into the foundations of mathematics, have also been dealt with.